Edge Detection Using Sobel Algorithm and YCbCr Colour Space Optimized on FPGA - An, Yang; Yuan, Qianqian; Zhang, Han (Informatica, 2025)
Edge detection plays a crucial role in image processing and computer vision, and is widely used in tasks such as object recognition and image segmentation. Traditional edge detection algorithms perform well in many applications, but there are still some shortcomings in terms of real-time performance and processing efficiency. To address this issue, a highly efficient image edge detection model combining Sobel algorithm and field programmable gate array technology was proposed. YCbCr color space conversion was performed on the image, then Sobel operator was utilized to calculate the image gradient, and adaptive thresholding method was applied to determine the edges. Finally, the model was implemented and optimized on a field programmable gate array. The experimental results showed that when the dataset size was 1000, the information retention rate of the proposed image preprocessing model was 0.89, and the structural information loss was 0.05. When the data volume was 100, the accuracy of the proposed image edge detection model was 0.90, and the root mean square error value was 0.16. The research results indicate that the proposed image edge detection model based on field programmable gate arrays has significant advantages in edge detection performance and processing efficiency. The model has high accuracy and speed in image edge recognition, which can provide certain guidance for research in the field of image edge detection